Russia and UNESCO: the Cooperation Guidelines - V. O. Rodionova (Vestnik MGIMO-Universiteta)
The article deals with UNESCO and Russia interacting. It is shown that the cooperation with UNESCO is favorably affecting an international image of Russia, and the fact contributes to strengthening conclusively the components of the Russia’s soft power. The author also concludes that it is necessary to go on with the formation of a national public diplomacy. An active cooperation with UNESCO certainly helps with achievement of the goal. It can be more actively used to solve important domestic political tasks as well: the establishment of democracy, the formation of the rule of law, the prophilaxis of ethnic and social conflicts.